Status of Dalit Women in Eastern Terai: A Post-Madhesh Movement and Federal Democracy Perspective - Oli, Jagadish (Nepalese Journal of Society and Culture, 2025)
This article examines the social condition of Madheshi Dalit women in eastern Terai following the Madhesh uprising of 2007, 2008, and 2015, as well as the establishment of Nepal’s federal democracy in 2006. This research examines how caste-based structures entrenched in Hindu traditions affect the lives of Madheshi Dalit women. The study concludes that the introduction of federal democracy and the Madheshi movement in Nepal had no substantial impact on the lives of Dalit women. Poverty, unemployment, violence, and discrimination based on gender and caste continued. According to the findings, the underdevelopment and poverty of Madheshi Dalit women are caused mainly by caste- and gender-based discrimination, social and economic isolation, and inequality. Nonetheless, the growing political participation of Dalit women activists has had a significant impact. Political rights are increasingly being recognised, and Dalit women are becoming more visible in local government agencies. As they battle for women’s representation and speak out against various forms of violence and social inequity, both within and outside of their communities, Dalit women’s voices are being heard more and more.